Indigenous immobilized nitrifying bacteria for reduction of ammonia in shrimp larviculture system - Natnan, Maya Erna (2012)
The shrimp industry has grown rapidly due to the increase in market demand, which in turn resulted in intensive shrimp postlarvae (PL) cultivation practices. The ultrahigh stocking densities and over loading of feeds cause serious water quality problems in PL hatchery system. Exposure of shrimp PLs to toxic compounds like ammonia leads to stress and diseases that eventually causes PL mortality. The present study investigated the ability of local indigenous immobilized nitrifying bacteria, isolated from the marine environment, to reduce total ammonia nitrogen (TAN) in a shrimp larviculture system. For isolation of nitrifying bacteria, soils and water samples were collected from the west coast of Peninsular Malaysia such as Kuala Juru, Kuala Gula, Morib and shrimp farms in Kuala Langat. Bacteria were grown in Skinner and Walker medium and then screened for their ability to reduce ammonia. Since nitrifying bacteria cannot be isolated in a pure culture condition,they were cultured and maintained as consortia. The nitrifying bacteria consortia were then tested for their ability to reduce ammonia and the consortium that showed the lowest ammonia reading was selected for further experiments. Consortium M1,isolated from the mangrove area of Morib, showed the best reduction rate (0.154mg/l/day) of ammonia from 2.0 ± 0.1 mg/l to 0.06 ± 0.01 mg/l in 14 days, when tested in the laboratory. Using 16S rDNA primers, three species of bacteria were identified from the consortium M1, namely Pseudomonas aeruginosa with 99% homology, Pseudomonas stutzeri with 98% homology and Nocardioides albus with 98% homology after BLAST analyses in Genebank. Further experiments were conducted to test the efficacy of the consortium M1 for its ability to reduce ammonia in a shrimp larviculture system. The bacteria consortium M1 was immobilized using alginate solution. Tanks treated with immobilized bacteria were able to achieve high ammonia reduction proficiency to 76.52%, followed by tanks that were replaced with 50% fresh seawater on alternate days (68.10 %), tanks treated with non-immobilized bacteria (36.84%) and tanks treated with alginate beads without bacteria (18.37%). However, in control tanks (without treatment) ammonia increased to 40.79% at 14 days. Tanks treated with immobilized bacteria has significantly (P < 0.05) increased survival rate (72.44%) and specific growth rate (SGR) (12.86%) of shrimp PL compared to other treatments.